Childhood Trauma and Psychosocial Stress Affect Treatment Outcome in Patients With Psoriasis Starting a New Treatment Episode - Wintermann, Gloria-Beatrice; Bierling, Antonie Louise; Peters, Eva M. J.; Abraham, Susanne; Beissert, Stefan; Weidner, Kerstin (Frontiers in Psychiatry, 2022)
Objective: Traumatic childhood experiences and psychosocial stress may predispose the evolvement of somatic diseases. Psoriasis is a multifactorial chronic inflammatory skin disease that often associates with current and past stress. Both may entail pathological alterations in major stress axes and a balance shift in the level of T helper type 1 (Th1) and 2 (Th2) cytokines, affecting the development and course of psoriasis. Until now, it is unclear whether traumatic stress experiences during the childhood or current stress are more frequent in psoriatic compared to skin-healthy individuals, and if they interact with treatment outcome. Method: In a prospective cohort study, the impact of acute and early childhood stress on the course of dermatological treatment were studied in patients with moderate to severe psoriasis (PSO). Patients were examined before (T1) and about three months after (T2) the beginning of a new treatment episode. Assessments included clinical outcomes (Psoriasis Area and Severity Index – PASI, Structured Clinical Interview SCID-I) and patient-reported outcomes (PRO) (Childhood Trauma Questionnaire-CTQ, Perceived Stress Scale-PSS, itching/ scratching, Dermatology Life Quality Index-DLQI, Hospital Anxiety and Depression Scale, Body Surface Area, Self-Administered PASI). Results: N = 83 PSO patients (median age 53.7, IQR 37.8, 62.5) and n = 66 skin-healthy control subjects (HC) (median age 51.5, IQR 33.3, 59.2) participated. PSO had higher CTQ physical neglect than HC, as well as higher PRO levels. The positive impact of improved skin on the skin-related quality of life was moderated by the perceived stress. Acute stress at T1 had a positive effect both on the skin severity and the skin-related quality of life. CTQ total closely interacted with baseline psoriasis severity, and was associated with higher improvement from T1 to T2. Conclusion: One might tentatively conclude, that chronic psychosocial stressors like childhood maltreatment may predispose the manifestation of psoriasis. The latter may be amplified by acute psychological stressors. In addition, the present evidence suggests that systemic therapies work well in PSO, with childhood trauma and acute psychosocial stress. Both should therefore be routinely assessed and addressed in PSO.